Play and Child Development: Considerations from a Comparative Ethnographic Research in Two Rural Argentinian Communities - Remorini, Carolina (2014)
In this paper, we present the preliminary results of an ongoing ethnographic research on childrearing and child development from an ecological approach among two rural Argentinean populations: an indigenous population (Mbya Guarani) located in the northeastern rainforest and a creole population (Molinos) located in the northwest highlands. The study adopts a comparative approach to children’s play activities. We analyze play as part of children’s formative experiences in the context of their participation in household activities and their relationships with adults and peers. We focus on aspects such as the role of movement and motor skills in children´s play; the characteristics of spaces and materials involved in children´s play; the playmates for babies and older children and the social value assigned to play in the context of household daily routines. The complementary use of different observation techniques, interviews and videotapes facilitated the recognition of ecological factors affecting children’s play in each setting, showing intra and intercultural variability. We selected several scenes recorded during fieldwork which are examples of contexts for play activities of children of different ages. Based on that, we identify the ecological factors affecting play including material and symbolic conditions that characterize the way of life of each enclave.